(untitled) (Principles and Practice of Clinical Research, 2022)
Introduction: This review aimed to investigate the effects of transcranial direct current stimulation (tDCS) on appetite, food intake, food craving, and body weight in people with obesity.Methods: Two independent reviewers conducted a systematic search in PubMed, Science Direct, and Bibiolteca Virtual em Saúde databases. All randomized controlled clinical trials that studied the effects of tDCS in at least one of the following outcomes: appetite, body weight changes, food intake, and food craving in adults with overweight or obesity, were included.Results: Fourteen studies were identified. Of those, six analyzed appetite, nine analyzed food intake, five analyzed food craving, and six analyzed body weight changes. All the studies considered the dorsolateral prefrontal cortex (DLPFC) as a target. The results reinforce the safety of this technique and point to a positive effect of the association of tDCS with other strategies for the management of obesity. Furthermore, they highlight the importance of understanding individual variability to promote beneficial results.Conclusions: This systematic review shows promising results regarding the use of tDCS in the treatment of obesity. However, the current literature is still controversial and differs between the tDCS protocols and the methods for evaluating the analyzed outcomes. Further studies are needed to better understand the mechanisms of action and individual effects of tDCS in people with obesity to enable its use in clinical practice.